The Effect of Aqueous and Alcoholic Extracts of Castor Leaves (Ricinus Communis L) on the Survival of the Mosquito (Diptera: Culicidae) Culex Pipens L. - Mazloum, Huda Ahmed Faisal; Abd Jouda, Zeina Najm; Abdul Alrahman, Wafa Faisal Najy; Ibrahim, Duaa Asaad Haider (American Journal of Biology and Natural Sciences, 2025)
This study examines the effect of extracts from Ricinus communis (castor plant) leaves (aqueous and alcoholic) on the immature stages of Culex pipiens mosquitoes under laboratory conditions. The results are as follows: The hot water extract of the plant leaves had a stronger effect than the cold water extract in terms of mortality rates for both eggs and the four larval stages as well as pupae. The egg mortality rates for hot and cold water extracts were recorded. 2. The ethyl alcohol extract also had an effect on the mortality of the immature stages of Cx. pipiens. The mortality rates for the first, second, third, and fourth larval stages were observed with the ethyl alcohol extract.